COMPARATIVE IMMUNOHISTOCHEMICAL ANALYSIS OF K-RAS ONCOGEN AND CYCLOOXYGENASE2 ENZYME EXPRESSION IN PLEOMORPHIC ADENOMA AND ADENOID CYSTIC CARCINOMA OF SALIVARY GLANDS - Merza, Muna S. (European Scientific Journal, ESJ, 2013)
Background: The salivary glands tumors constitute an important area in the field of oral and maxillofacial pathology. Although, such tumors are uncommon, thus they are not rare. Pleomorphic adenoma is the most common salivary benign tumor and from a histological point of view, it contains the epithelial cell, the myo-epithelial cell and mesenchymal ingredient. Adenoid cystic carcinoma is an infiltrative malignant salivary gland tumor with three different histological patterns: cribriform, tubular or solid. RAS is a signal transduction protein for various important cellular processes such as cellular proliferation, differentiation, and survival by mediating the cell's response to extracellular stimulations. K-ras is a protein within the RAS family, and it functions in the same pathway of a Ras –Raf - Mek-Erk-map kinase pathway which plays a role in mediating cellular response to cell growth. K-ras appears to be involved in signal transduction and cell cycle regulation. Cyclooxygenase-2, an inducible enzyme in most cell types including keratinocytes, fibroblast and Tcell, catalyzes the synthesis of prostaglandins. Several processes in cancer may be influenced by Cox-2 including cell proliferation, apoptosis, and angiogenesis. Therefore, cyclooxygense2 may inhibit apoptosis via different pathways like down- regulation of arachidonic, up regulation of proto-oncogene Bcl2 and down-regulation of Bax, thus contributing to an increased survival rate. Aims of the study: This study was conducted to analyze the expression of K-ras oncogen and Cox-2 enzyme in pleomorphic adenoma and adenoid cystic carcinoma of salivary glands and to correlate the expression of the aforementioned biomarkers with the clinical parameters, histological subtypes and components, and with each other as well. Materials and Methods: In this study, 24paraffin embedded tissue blocks of salivary gland tumors were selected retrospectively from the files of the department of Oral pathology at the College of Dentistry, Baghdad University; 12 cases were pleomorphic adenoma and the other 12 cases were adenoid cystic carcinoma. Immunohistochemistry technique was used to assess K-ras oncogen and Cox-2 enzyme expression in these tumors. Results: Positive K-ras immunohistochemical expression was found in 11 (91.6%) and 8 (66.6%) of pleomorphic adenoma and adenojd cystic carcinoma studied cases respectively. Regarding Cox-2 expression, the results showed positive expression in 7 (58.3%) and1 (91.6 %) of pleomorphic adenoma and adenoid cystic carcinoma studied cases respectively. Statistically significant correlation was shown regarding K-ras expression with the sex of pleomorphic adenoma (P 0.044), while nonsignificant correlation was observed with other clinical parameters in pleomorphic adenoma and adenoid cystic carcinoma. Concerning Cox-2 expression, statistically significant correlation revealed with the site of pleomorphic adenoma (P 0.046) and the sex of adenoid cystic carcinoma (P 0.02), while non-significant correlation was found with other clinical parameters of both tumors. Conclusion: The present study showed a highly expression rate of K-ras in pleomorphic adenoma and highly expression rate of Cox-2 in adenoid cystic carcinoma. The results also showed that there is no significant correlation between the expression rate of both K-ras and Cox-2 among study cases.